Extra-aural disorders in patients with acoustic trauma who were in the zone of the antiterrorist operation. - T. A. Shidlovs’ka; L. G. Petruk (Medičnì Perspektivi)
The incidence of acoustic trauma is growing in our country in connection with the situation in the east of Ukraine. Increased number of auditory system damage resulting from mine blast and other types of acoustic trauma, including those received in real combat conditions, makes the demand to provide quick and timely support to such patients. Also it is important to prevent the development of severe lesions and disability of acoustic analyzer. In this context it is important to study not only the state of various parts of the auditory system, but also the data of the organs and systems activity, that influence the auditory analyzer - extra-aural violations. The article presents the characteristics of auditory function of 59 patients with acoustic trauma who were in the ATO zone. Cerebral blood flow and brain activity was studied by methods of rheoencephalography (REG) and electroencephalography (EEG) with the help of a computer analyzing system «DX - system" (Ukraine). Researches have shown that patients with acoustic trauma who were in the ATO zone had pronounced violations in the bioelectrical brain activity and cerebral hemodynamics. Studies evidenced the presence of pronounced changes in the state of brain activity in the examined patients. According to the obtained data, all patients with acoustic trauma who were in the ATO zone had the cortical brain structures irritation, pronounced irritative biocurrent changes and disruption of basic EEG rhythms. In the surveyed patients there were identified processes of cortical rhythms desynchronization, their disorganization and tendency to zonal difference smoothness, percentage distortion of basic EEG rhythms as compared to the norm, reduction of the alpha-rhythm and growth slow of wave activity, especially in the front projections; is testifies to dysfunction primarily of stem-diencephalic brain structures. Diencephalic structures irritation was detected in 54,2%, stem-diencephalic - in 30,5% of cases. According to REG in the studied patients with acoustic trauma who were in the ATO zone, we found significant changes in cerebral blood flow. Along with difficulty of the venous outflow, increased cerebral vascular tonus, vasoconstriction phenomena typical to SHL, instability cases (47,5%) and decrease (42,4%) of cerebral vascular tonus, were revealed, this distinguishes this SHL type from other ones. The obtained data will be useful in the diagnosis and target treatment of patients with acoustic trauma because they takes into account extra-aural changes and help to improve therapeutic and preventive measures effectiveness. The results of this work demonstrate the advisability of the rheoencephalography and electroencephalography methods in examining patients with acoustic trauma who were in the ATO zone with the aim of further integration during the treatment. Usage of such survey results allows to prove targeted and timely treatment of patients with acoustic trauma and to provide its effectiveness. The findings deepen our knowledge about the role of cerebral circulation and brain activity in the development of sensoneural hearing impairment in acoustic trauma in real combat conditions.